PANCASILA AS A GUIDELINE FOR THE YOUNG GENERATION IN FACING GLOBAL CHALLENGES - Rambe, Adestia Salwa; Sinaga, Rudi Salam (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Pancasila, as the foundation of the Indonesian state, plays a vital role in guiding the younger generation through the challenges of globalization. Amid the rapid flow of information and foreign cultural influences, Indonesian youth face threats such as declining nationalism, rising individualism, and weakened communal values. The five principles of Pancasila offer a moral and ideological compass that remains relevant in preserving national identity. Early education on Pancasila is essential in shaping character and increasing national awareness among young people. By internalizing and practicing Pancasila values in daily life, the younger generation can confront global challenges without losing their cultural identity.